HUBUNGAN ANTARA PERSEPSI TENTANG HIV/AIDS DAN STIGMA TERHADAP ODHA PADA MAHASISWA KESEHATAN FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Prihartini, Ni Made Listya; Nurhesti, Putu Oka Yuli; Antari, Gusti Ayu Ary (Coping: Community of Publishing in Nursing; Vol 10 No 3 (2022): Juni 2022, 2022)
Stigma is the one of negatif impacts of HIV/AIDS that can be an obstacle in prevention and treatment of People Living with HIV (PLWH). Stigma against PLWH affected by a person's perception. Health providers and health science students should provide health services without discrimination. This study aimed to determine the correlation between perception of HIV/AIDS and stigma against PLWH among health science students of Faculty of Medicine, Udayana University. This study was a correlative descriptive study. Sampling techniques in this study was proportionate stratified random sampling with 269 respondents who are 4 th grade students in Faculty of Medicine, Udayana University. The data about perception and stigma were collected using a using a perception questionnaire that refers to the theory of Health Belief Model (HBM) and a stigma questionnaire adopted from the Development of a Brief Scale to Measure AIDS-related Stigma. Median of the respondents’ perception is 91.00 with a variant of 38,542 and the median of the respondents’ stigma is 9.00 with a variant of 5.027. The result of the statistical test shows a significant correlation between perceptions of HIV/AIDS and stigma towards PLWH in health science students of the Faculty of Medicine, Udayana University (p value = 0,000; ? = 0,05; r = -0,351).